2022
DOI: 10.1038/s41598-021-04636-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of airway fire with the use of KTP laser and high flow humidified oxygen delivery in a laryngeal surgery model

Abstract: Airway surgery presents a unique environment for operating room fire to occur. This study aims to explore the factors of combustion when using KTP laser with high flow oxygen in an ex-vivo model. The variables tested were varying tissue type, tissue condition, oxygen concentration, laser setting, and smoke evacuation in a stainless-steel model. Outcome measures were time of lasing to the first spark and/or flame. A multivariate Cox proportional hazard model was used to determine the risk of spark and flame acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Short, intermittent use of laser in pulsed mode along with low O 2 levels is thought to be safe, with a low risk of ignition or fire. 13,14 To summarize, there are limited prospective data on physiological and vital parameters of the use of THRIVE in laryngeal surgeries in a larger adult population. No data exist on the use of THRIVE in lower oxygen concentrations that is, 30%, in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short, intermittent use of laser in pulsed mode along with low O 2 levels is thought to be safe, with a low risk of ignition or fire. 13,14 To summarize, there are limited prospective data on physiological and vital parameters of the use of THRIVE in laryngeal surgeries in a larger adult population. No data exist on the use of THRIVE in lower oxygen concentrations that is, 30%, in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al 13 demonstrated the risk of self‐sustained airway fires at oxygen concentrations >80% using a continuous wave fiber laser but noted episodes of ignition even at lower O 2 levels. Huang et al 14 showed the risk of sparks and flame when using the laser with high flow oxygen increases with higher delivered oxygen concentrations (>60%), continuous potassium‐titanyl‐phosphate (KTP) laser settings, charred tissue, and lasering adipose tissue. Short, intermittent use of laser in pulsed mode along with low O 2 levels is thought to be safe, with a low risk of ignition or fire 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Stuermer et al found in experimental models of fat, muscle, and cartilage that limiting laser use to intervals of 5 seconds in conditions of 50% oxygen or lower prevented fire from occuring 10 . Experiments with in vitro models suggest that reducing the oxygen concentration, using pulsed modes with low wattages, limiting lasing times, and eliminating certain endolaryngeal material can reduce the operative fire risk 11‐13 …”
mentioning
confidence: 99%
“…Finally, organic tissue models use tissues derived from outside the airway. 8 Given these limitations, the objective of this study was to design an organic airway tissue model to establish ideal conditions for starting an airway fire.…”
mentioning
confidence: 99%
“…Mannequin models allow for simulations that have structures closest to the human airway, but are not composed of organic tissue. Finally, organic tissue models use tissues derived from outside the airway 8 . Given these limitations, the objective of this study was to design an organic airway tissue model to establish ideal conditions for starting an airway fire.…”
mentioning
confidence: 99%